2021
DOI: 10.48550/arxiv.2104.06453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Properties of Faint X-ray Activity of XTE J1908+094 in 2019

Debjit Chatterjee,
Arghajit Jana,
Kaushik Chatterjee
et al.

Abstract: We study the properties of the faint X-ray activity of Galactic transient black hole candidate XTE J1908+094 during its 2019 outburst. Here, we report the results of detailed spectral and temporal analysis during this outburst using observations from Nuclear Spectroscopic Telescope Array (NuSTAR). We have not observed any quasi-periodic-oscillations (QPOs) in the power density spectrum (PDS). The spectral study suggests that the source remained in the softer (more precisely in soft-intermediate) spectral state… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Still, both papers concluded that spin measurements cannot be made using the dataset. The 2019 NuSTAR observation was analyzed in Chatterjee et al 2021, but no attempt at a spin measurement was made. Motivated by the characteristics of NuSTAR such as its wide pass band and its high sensitivity and by previous similar spin measurements using relativistic reflection (see e.g., King et al 2014;El-Batal et al 2016;Draghis et al 2020;Xu et al 2020), we revisited the 2013 and 2019 observations of XTE J1908+094.…”
Section: Introductionmentioning
confidence: 99%
“…Still, both papers concluded that spin measurements cannot be made using the dataset. The 2019 NuSTAR observation was analyzed in Chatterjee et al 2021, but no attempt at a spin measurement was made. Motivated by the characteristics of NuSTAR such as its wide pass band and its high sensitivity and by previous similar spin measurements using relativistic reflection (see e.g., King et al 2014;El-Batal et al 2016;Draghis et al 2020;Xu et al 2020), we revisited the 2013 and 2019 observations of XTE J1908+094.…”
Section: Introductionmentioning
confidence: 99%